(untitled) (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to estimate the genetic distance of irrigated rice based on different phenotypic characters and agronomic descriptors in field experiments and a greenhouse, with joint analysis of environments. In this study, 16 genotypes of rice were evaluated in the field and in greenhouse. In both experimental conditions were measured 24 characters, 16 considered quantitative and eight qualitative. From the phenotypic data were obtained three matrices of Mahalanobis distances (based on characters measured for field, greenhouse and joint analysis), which originated three dendrograms using the Unweighted Pair Group Method using Arithmetic averages (UPGMA). The correlation between genetic distance matrices was performed by the Mantel test. Thus, the estimates of genetic distance used were adequate in the grouping of genotypes, evidencing a narrow genetic distance between the irrigated rice cultivars evaluated. The genetic distance matrices between genotypes based on the qualitative characteristics measured for field, greenhouse and joint analysis of both environments showed a high correlation. There is environmental effect on characteristics of quantitative genetic inheritance.